Jacalin interaction with human immunoglobulin A1 and bovine immunoglobulin G1: Affinity constant determined by piezoelectric biosensoring - Pedroso, Mariele M.; Pesquero, Naira C. [UNESP]; Thomaz, Sandra M. O. [UNESP]; Roque-Barreira, Maria C.; Faria, Ronaldo C.; Bueno, Paulo Roberto [UNESP] (Oxford University Press, 2012)
The affinity of the d-galactose-binding lectin from Artocarpus heterophyllus lectin, known as jacalin, with immonuglobulins (Igs) was determined by biofunctionalization of a piezoelectric transducer. This piezoelectric biofunctionalized transducer was used as a mass-sensitive analytical tool, allowing the real-time binding analysis of jacalin-human immunoglobulin A1 (IgA(1)) and jacalin-bovine IgG(1) interactions from which the apparent affinity constant was calculated. The strategy was centered in immobilizing jacalin on the gold electrode's surface of the piezoelectric crystal resonator using appropriate procedures based on self-assembling of 11-mercaptoundecanoic acid and 2-mercaptoethanol thiol's mixture, a particular immobilization strategy by which it was possible to avoid cross-interaction between the proteins over electrode's surface. The apparent affinity constants obtained between jacalin-human IgA(1) and jacalin-bovine IgG(1) differed by 1 order of magnitude [(8.0 +/- 0.9) x 10(5) vs (8.3 +/- 0.1) x 10(6) L mol(-1)]. on the other hand, the difference found between human IgA(1) and human IgA(2) interaction with jacalin, eight times higher for IgA(1), was attributed to the presence of O-linked glycans in the IgA(1) hinge region, which is absent in IgA(2). Specific interaction of jacalin with O-glycans, proved to be present in the human IgA(1) and hypothetically present in bovine IgG(1) structures, is discussed as responsible for the obtained affinity values.
Keywords: Apparent affinity constant; immunoglobulin; jacalin; lectin; QCM